1996
DOI: 10.1111/j.1600-0749.1996.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin Receptors: Identification and Characterization by Melanotropic Peptide Agonists and Antagonists

Abstract: Hormones are chemical messengers released from cells to act on and control the activity of other cells. Hormonal ligands initiate their actions by interacting with receptive substances (Langley, 1906) of the target cells. These receptors are proteins that are either integral components of the cell membrane or are localized cytoplasmically within cells. Ligand-receptor interaction results in either the stimulation or inhibition of cellular activity. Since most hormones bind rather specifically to receptors poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 111 publications
0
27
0
Order By: Relevance
“…For the assay, the medium was removed and cells were washed twice with a freshly prepared binding buffer containing 100% minimum essential medium with Earle's salt (MEM, GIBCO), 25 mM HEPES (pH 7.4), 0.2% bovine serum albumin, 1 mM 1,10-phenanthrolone, 0.5 mg/L leupeptin, and 200 mg/L bacitracin. Cells were then incubated with different concentrations of unlabeled peptides and 125 I-labeled [Nle4,DPhe7]-α-MSH (PerkinElmer Life Science, 100, 000 cpm/well, 0.1386 nM) for 40 min at 37 °C. The medium was subsequently removed and each well was washed twice with the binding buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assay, the medium was removed and cells were washed twice with a freshly prepared binding buffer containing 100% minimum essential medium with Earle's salt (MEM, GIBCO), 25 mM HEPES (pH 7.4), 0.2% bovine serum albumin, 1 mM 1,10-phenanthrolone, 0.5 mg/L leupeptin, and 200 mg/L bacitracin. Cells were then incubated with different concentrations of unlabeled peptides and 125 I-labeled [Nle4,DPhe7]-α-MSH (PerkinElmer Life Science, 100, 000 cpm/well, 0.1386 nM) for 40 min at 37 °C. The medium was subsequently removed and each well was washed twice with the binding buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we designed MTII and SHU9119 analogues 2 , 3 , 7 , 8 in which the Arg8 residues in their core sequences were replaced by 4- trans - or cis -guanidinyl-Pro residues (Figure 2). Additionally, to test how this modification compares with a potent nonselective linear peptide, Ac-NDP-γ-MSH-NH 2 (Ac-Tyr1-Val2-Nle3-Gly4-His5-DPhe6-Arg7-Trp8-Asp9-Arg10-Phe11-Gly12-NH 2 ),49 analogues 12 , 13 were designed which contained a trans - or cis -4-guanidinyl-Pro in the key arginine7 positions (Figure 2). For comparison, control analogues 1 , 6 and 11 were also synthesized to investigate the importance of the guanidinyl groups.…”
Section: Design Of Novel Ligandsmentioning
confidence: 99%
“…Five MCRs (MCR1-MCR5) have been identified (1,7,11). Of these MCRs, only MCR4 and to a lesser extent MCR3 have been identified in the central nervous system (CNS).…”
mentioning
confidence: 99%
“…18 To overcome these issues, we used a stable, potent analog, NDPMSH. 12 To determine the various pharmacokinetic parameters of this compound, the iodinated compound was ®rst examined with respect to structure and ef®cacy. Puri®cation of commercially prepared cold iodinated NDPMSH was performed to separate the mono-iodinated form from the di-iodinated and uniodinated NDPMSH.…”
Section: Rationale For Using Ndpmshmentioning
confidence: 99%
“…8,10 Recently, we have shown that agouti antagonizes the MC4R and MC3R receptors with K i 's closer than originally described. 11 In order to test the hypothesis that agouti antagonism of MCRs leads to these phenotypes we introduced norleucine, 4 D-phenylalanine 7 aMSH (NDPMSH), a potent ligand and agonist of all the MCRs, 11,12 into transgenic mice ubiquitously overexpressing the wild type agouti protein. We report here that while the NDPMSH showed good systemic effects on coat coloration and core temperature regulation, it failed to have any effect on insulin, glucose levels and weight.…”
Section: Introductionmentioning
confidence: 99%